Penentuan Penerimaan Karyawan Menggunakan Metode Simple Additive Weighting dan Weight Product - Ermin Al Munawar; Sunardi Sunardi; Abdul Fadlil (Universitas Diponegoro, 2021)
Recruitment errors influence in a decrease of quality, performance, and company revenue. One of the causes is the absence of a method that is applied as a systematically of information system in determining the acceptance of the best prospective employees. This study uses the Simple Additive Weighting (SAW) and Weight Product (WP) methods to build an objective, fast, and accurate of Decision Support System (DSS) in determining employee acceptance. This research case study was applied to the Indonesian Market Traders Cooperative (KOPPI) Sorong City, West Papua Province by involving a number of 10 alternative applicants. This study aims to produce an objective information system and provide convenience in determining the best employees, referring to the determination of 9 criteria obtained from interviews, namely education, work experience, motivation, intrapersonal ability, achievement orientation, sales ability, self-confidence, trustworthy, and work ethic by weighting each. SAW and WP methods are both used to determine the best ranking of all alternative applicants and get the best prospective employees. The information system was built using the Waterfall development method with the PHP programming language and Mysql database. Based on the results of research that has been carried out, it is found that the information system built has 100% conformity of functionality and compatibility between manual and application system. Both methods provide the same highest alternative to be used as the determination of the best employee acceptance, however it is found that the WP method provides better accuracy and validity than SAW.